An online multiple-choice micro-biology game for under-graduate medical students: a case study - Struwig, Daleen; Beylefeld, Adri; Hugo, Alwyn; Joubert, Gina (Acta Academica: Critical views on society, culture and politics, 2012)
Educational games are increasingly used in medical curricula to enhance the process of mastering subject content. Students experience medical microbiology as an exceptional challenge because of unfamiliar terminology and the extensive volume of this field of study. Consequently, many students believe that medical microbiology could be a major contributor to failing an academic year. This article describes the use of an online multiple-choice game to improve students’ performance in the Infections module of their medical training programme. The results show that an informal approach to learning may be beneficial to students, even in tertiary institutions.